Vojeslav Mole - Žitnik Serafin, Janja (Dve domovini, 1996)
Based on the published literary works by the Slovene emigrant poet, writer and renowned historian Vojeslav Mole, as well as scientific and profesional publications on his work, this article provides a short overview of Mole's life and work. His scientific works being better known than his literary opus, this article focuses more on the later.
Keywords: art history; biografije; Mole, Vojeslav, 1886-1973; Poland; Poljska; slovenski izseljenci; slovenski pesniki; slovenski pisatelji; umetnostna zgodovina; United States of America; ZDA